1997
DOI: 10.1259/bjr.70.833.9227234
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy in the treatment of solitary plasmacytoma.

Abstract: Solitary plasmacytoma of bone (SPB) and extramedullary plasmacytoma (EMP) are rare. High local control rates are reported with radiotherapy, although the optimal dose and extent of radiotherapy portals remains controversial. Between 1983 and 1993, 30 patients with solitary plasmacytoma were seen at the Regional Cancer Centre, Trivandrum, India. 23 patients had SPB and seven EMP. The mean age was 52 years and the male to female ratio 3.2:1. Diagnosis of SPB was confirmed by biopsy in 16 patients and tumour exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 17 publications
2
56
0
3
Order By: Relevance
“…Data published so far are inconsistent: Significantly different OS rates were found by Ozsahin et al, who described 10-year overall survival rates of 72% for EP and 52% for SBP (p=0.04) [4], and Tsang et al, who reported 8-year overall survival rates of 70% or 33%, respectively (p=0.023). In contrast, neither Bolek et al [12] nor Jyothirmay et al [13] could detect a significant difference in OS.…”
Section: Overall Survivalmentioning
confidence: 84%
“…Data published so far are inconsistent: Significantly different OS rates were found by Ozsahin et al, who described 10-year overall survival rates of 72% for EP and 52% for SBP (p=0.04) [4], and Tsang et al, who reported 8-year overall survival rates of 70% or 33%, respectively (p=0.023). In contrast, neither Bolek et al [12] nor Jyothirmay et al [13] could detect a significant difference in OS.…”
Section: Overall Survivalmentioning
confidence: 84%
“…The overall 10 year survival rate ranges from 45 to 100 %, the difference is in accordance with the rate of conversion to Multiple myeloma [7,[11][12][13][14].…”
Section: Case Reportmentioning
confidence: 88%
“…Hemoptysis, always scanty and episodic, is rather common and more disturbing for clinicians. 3,7,11,12 Reyhan et al The mass lesion has the same density as the thyroid tissue and has marked homogeneous enhancement after intravenous contrast agent administration (arrow). B, On virtual bronchoscopic images, the tracheal lumen is markedly narrowed by the mass.…”
Section: Discussionmentioning
confidence: 99%